(untitled) (INTEGRATION PROCEEDING, 2023)
The incidence of breast cancer increases with age. However, young age is also not a guarantee from breast cancer. The simplest way to detect breast lumps early is to identify your own breasts through breast self-examination (BSE). The focus in this study is PMT (protection motivation theory) on early detection of breast cancer. The purpose of this study was to determine the knowledge and behavior of students of the Bachelor of Pharmacy Study Program at Sari Mulia University in carrying out early detection of breast cancer with PMT theory. The sample in this study was 74 female students and this research was conducted using a quantitative descriptive method with a cross sectional study approach using a questionnaire which was analyzed by univariate. The results of this study obtained 91% of respondents have good knowledge and only 9% of respondents with poor knowledge. Respondents with good knowledge can try to do early detection of breast cancer. With PMT analysis which consists of 4 domains, that are severity, vulnerability, response effectiveness, and self-efficacy. From the results of respondents’ answers, the existence of the four domains can be identified in the factors causing respondents to carry out self-protection efforts from breast cancer with the BSE method